Adults with Cerebral Palsy have Higher Prevalence of Fracture Compared with Adults Without Cerebral Palsy Independent of Osteoporosis and Cardiometabolic Diseases. (6th March 2019) - Whitney, Daniel G; Alford, Andrea I; Devlin, Maureen J; Caird, Michelle S; Hurvitz, Edward A; Peterson, Mark D
ABSTRACT: Individuals with cerebral palsy (CP) have an increased risk of fracture throughout their lifespan based on an underdeveloped musculoskeletal system, excess body fat, diminished mechanical loading, and early development of noncommunicable diseases. However, the epidemiology of fracture among adults with CP is unknown. The purpose of this cross‐sectional study was to determine the prevalence of fracture among a large sample of privately insured adults with CP, as compared with adults without CP. Data were from the Optum Clinformatics Data Mart (Eden Prairie, MN, USA), a deidentified nationwide claims database of beneficiaries from a single private payer. Diagnostic codes were used to identify 18‐ to 64‐year‐old beneficiaries with and without CP and any fracture that consisted of osteoporotic pathological fracture as well as any type of fracture of the head/neck, thoracic, lumbar/pelvic, upper extremity, and lower extremity regions. The prevalence of any fracture was compared between adults with ( n  = 5, 555) and without ( n  = 5.5 million) CP. Multivariable logistic regression was performed with all‐cause fracture as the outcome and CP group as the primary exposure. Adults with CP had a higher prevalence of all‐cause fracture (6.3% and 2.7%, respectively) and fracture of the head/neck, thoracic, lumbar/pelvic, upper extremity, and lower extremity regions compared with adults without CP (all p < 0.01). After adjusting for sociodemographic and socioeconomic variables, adults with CP had higher odds of all‐cause fracture compared with adults without CP (OR 2.5; 95% CI, 2.2 to 2.7). After further adjusting for cardiometabolic diseases, adults with CP had higher odds of all‐cause fracture compared with adults without CP (OR 2.2; 95% CI, 2.0 to 2.5). After further adjusting for osteoporosis, adults with CP still had higher odds of all‐cause fracture compared with adults without CP (OR 2.0; 95% CI, 1.8 to 2.2). These findings suggest that young and middle‐aged adults with CP have an elevated prevalence of all‐cause fracture compared with adults without CP, which was present even after accounting for cardiometabolic diseases and osteoporosis. © 2019 American Society for Bone and Mineral Research.